The cell wall‐targeted purple acid phosphatase AtPAP25 is critical for acclimation of Arabidopsis thaliana to nutritional phosphorus deprivation. (November 2014) - Del Vecchio, Hernan A.; Ying, Sheng; Park, Joonho; Knowles, Vicki L.; Kanno, Satomi; Tanoi, Keitaro; She, Yi‐Min; Plaxton, William C.
Summary Plant purple acid phosphatases (PAPs) belong to a relatively large gene family whose individual functions are poorly understood. Three PAP isozymes that are up‐regulated in the cell walls of phosphate (Pi)‐starved (−Pi) Arabidopsis thaliana suspension cells were purified and identified by MS as AtPAP12 (At2g27190), AtPAP25 (At4g36350) and AtPAP26 (At5g34850). AtPAP12 and AtPAP26 were previously isolated from the culture medium of −Pi cell cultures, and shown to be secreted by roots of Arabidopsis seedlings to facilitate Pi scavenging from soil‐localized organophosphates. AtPAP25 exists as a 55 kDa monomer containing complex NX(S/T) glycosylation motifs at Asn172, Asn367 and Asn424. Transcript profiling and immunoblotting with anti‐AtPAP25 immune serum indicated that AtPAP25 is exclusively synthesized under −Pi conditions. Coupled with potent mixed‐type inhibition of AtPAP25 by Pi (I50 = 50 μm), this indicates a tight feedback control by Pi that prevents AtPAP25 from being synthesized or functioning as a phosphatase except when Pi levels are quite low. Promoter–GUS reporter assays revealed AtPAP25 expression in shoot vascular tissue of −Pi plants. Development of an atpap25 T‐DNA insertion mutant was arrested during cultivation on soil lacking soluble Pi, but rescued upon Pi fertilization or complementation with AtPAP25. Transcript profiling by quantitative RT‐PCR indicated that Pi starvation signaling was attenuated in the atpap25 mutant. AtPAP25 exhibited near‐optimal phosphatase activity with several phosphoproteins and phosphoamino acids as substrates. We hypothesize that AtPAP25 plays a key signaling role during Pi deprivation by functioning as a phosphoprotein phosphatase rather than as a non‐specific scavenger of Pi from extracellular P‐monoesters.